Study of aeration efficiency at weirs - Baylar, Ahmet; Ba?atur, Tamer (Scientific and Technical Research Council of Turkey, 2000)
The amount of dissolved oxygen (DO) in the waters of rivers and streams is very important to the quality and existence of aquatic life. Hydraulic structures have an impact on the amount of dissolved oxygen in a river system, even though the water is in contact with the structure for only a short time. The same quantity of oxygen transfer that normally would occur over several kilometers in a river can occur at a single hydraulic structure. The primary reason for this accelerated oxygen transfer is that air is entrained into the flow, which produces a large number of bubbles. These air bubbles greatly increase the surface area available for mass transfer. Plunging overfall jets from weirs are a particular instance of this, and the aeration properties of such structures have been studied widely in the laboratory and field over a number of years. This study investigates weirs having different cross-sectional geometry and how they affect the aeration performance. It is demonstrated that the aeration efficiency of the triangular notch weir is generally better than the other weirs.
Keywords: Aeration; Aeration efficiency; Dissolved oxygen; Oxygen transfer; Weirs